Traffic Parameter Sensitivity in the Development of Site-specific Load Models. (2016) - Nowak, Marcel; Fischer, Oliver
Abstract: In the context of an aging infrastructure in a highly developed country like Germany and the resulting increased importance of reassessment of existing bridge structures, a need for more realistic and precise descriptions of traffic load impact (road traffic) on bridges arises. To address this necessity, a research project has been initiated in cooperation with the Highways Authority of Southern Bavaria, aiming at developing site-specific traffic load models and evaluating their potential of application within the scope of reassessment for an exemplary route, the federal highway BAB A92 in Germany. Based on large sets of recorded traffic data provided from permanent measurement stations, extensive numerical traffic simulations are performed. By evaluation of the structural response for selected bridge systems due to this simulated traffic and subsequent statistical extrapolation to extreme load effects, characteristic values of traffic load effects with defined return periods in accordance with requirements from the Eurocode are obtained, serving as base for calibration of site-specific load models. Extensive numeric parameter studies estimating extreme load effects on a set of different structures and traffic constellations are performed, to gain a better understanding of the underlying correlations, and hence support the development of strategies to identify those sections of the highway network promising the highest potential for the application of site-specific load models in bridge reassessment. This paper presents a general approach for developing site-specific load models based on recorded traffic data, and discusses first findings and results gained from the above described parameter study.